Pengaruh Profitabilitas, Likuiditas, Ukuran Perusahaan Dan Struktur Aktiva Terhadap Struktur Modal: Studi Empiris pada Perusahaan Sub Sektor Retailing yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Ramandani, Firman; Hakim, Astrid Dita Meirina (CV. ULIL ALBAB CORP, 2024)
This research aims to determine the effect of profitability, liquidity, firm size, and asset structure on capital structure in the retailing sub-sector companies listed on the Indonesia Stock Exchange for the period 2019–2023. The sample for this research consists of 16 companies in the retailing sub-sector listed on the Indonesian Stock Exchange during the 2019–2023 period. This study utilizes panel data regression analysis, with the help of the Eviews version 12 program and Microsoft Excel 2017. The findings indicate that profitability, firm size, and asset structure have no significant effect on capital structure. However, liquidity is found to have a negative and significant influence on capital structure.